Sworn to protect - Mills, DiAnn (Mills, DiAnn. Call of duty, 2010)
Two years ago, her husband was shot and killed trying to help undocumented immigrants, the very people Danika, a Border Patrol agent, is responsible for deporting. His murder was never solved. Now a recent string of attacks and arrests leads Danika to believe her husband's death may have been part of a larger conspiracy, and it appears that she's the next target. With the help of the only person she can trust she searches for answers before more innocent lives are destroyed.